Socio-economic position across the lifecourse and risk of breast cancer: findings from EPIC-Italy. (13th November 2019) - Berger, E; Krogh, V; Palli, D; Panico, S; Sacerdote, C; Tumino, R; Vineis, P; Severi, G; Castagné, R; Delpierre, C
Abstract: Backgrounds: Socio-economic position (SEP) is linked to many health outcomes but the link between SEP and breast cancer (BC) is complex. This study explores the relationship between SEP from early life and future risk of BC. Methods: We used data from the Italian component of the European prospective investigation into cancer and nutrition: EPIC-Italy (up to 26, 391 women). Cox proportional hazard models were used to estimate the association between measures of life course SEP (father's occupation, educational level, highest household occupation) with risk of BC, adjusting for health behaviours (smoking, alcohol, physical activity, Mediterranean diet), height, weight and reproductive factors (postmenopausal status, age at first full term pregnancy). To mimic life course experiences, we analysed the relationship between father's occupation and risk of BC, sequentially adjusting for SEP in young adulthood and adulthood, as well as the impact of social mobility. Results: We observed a significant association between father's occupation and risk of BC, where participant with low SEP had lower risk to develop BC (HR[95%CI] = 0.88[0.78; 0.99]). This association was borderline significant when we analysed educational level and highest household occupation. These associations were only slightly modified after adjustment for health behaviours, height and weight but more strongly affected by reproductive factors. However, the association between father's occupation and BC remained borderline significant in the fully adjusted model (HR[95%CI] = 0.91[0.80; 1.03]). Stable low trajectory showed a lower risk of BC (HR[95%CI] = 0.82[0.71; 0.96]) slightly attenuated after adjusted for reproductive factors (HR[95%CI] = 0.88 [0.75; 1.03]). Conclusions: Our findings suggest that low early-life SEP and stable low trajectory are associated with a lower risk of BC, which is partly explained by reproductive factors. Key messages: Low early life socioeconomic position and stable low trajectory are associated with a lower risk of BC. Reproductive factors, especially age at the first full term pregnancy, explain part of these associations.